The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1097/bpo.0000000000000125
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Pediatric Orthopaedic Information on the Internet

Abstract: Background Many patients use the Internet for health information. However, there are few guarantees to the reliability and accuracy of this information. This study examined the quality and content of Internet webpages for ten common pediatric orthopedic diagnoses. Methods We identified ten common diagnoses in pediatric orthopedics: brachial plexus injury, cerebral palsy, clubfoot, developmental dysplasia of the hip, leg length discrepancy, osteochondroma, polydactyly, scoliosis, spina bifida, and syndactyly.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 14 publications
1
27
0
Order By: Relevance
“…When we scanned the literature, we encountered a large number of publications on evaluating video quality of different branches and diseases and all of them concluded that the accuracy of the information and quality of the videos were poor. The results of our study were consistent with the results of those studies [17][18][19][20][21][22][23][24][25].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…When we scanned the literature, we encountered a large number of publications on evaluating video quality of different branches and diseases and all of them concluded that the accuracy of the information and quality of the videos were poor. The results of our study were consistent with the results of those studies [17][18][19][20][21][22][23][24][25].…”
Section: Discussionsupporting
confidence: 93%
“…There are various studies in the literature on orthopedic disorders and their surgical treatments, including distal radius fracture [20], carpal tunnel syndrome [21], pediatric orthopedics [19], cervical disk herniation [22], spinal stenosis treatment [29], and knee arthroscopy and injuries [18]. In these studies, popular search engines (Google/Yahoo/Yandex) were investigated instead of YouTube.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27][28] Nonprofit and academic Web sites have been found to be the most reliable sources, whereas commercial and physician-run Web sites are the least reliable. 29 Our aim was to evaluate both online and textbook information to provide a more comprehensive survey of available information. Our study was unique in the evaluation of pediatric fracture information in particular and in the incorporation of the recently published AAOS guidelines to serve as gold standards.…”
Section: Discussionmentioning
confidence: 99%
“…As the ongoing challenge of parents who refuse to vaccinate their children attests, some people might be immune to this form of rational argument [15,16]. Moreover, the increasing availability and accessibility of unfiltered and unvetted information obtained from sources on the internet-including websites, blogs, social media networks, and the like-can radically affect the ability of physicians to counter preformed and deeply held beliefs with more reliable and trustworthy data [17][18][19].…”
Section: Making Decisions For Childrenmentioning
confidence: 99%